2006
DOI: 10.1007/bf02698065
|View full text |Cite
|
Sign up to set email alerts
|

What motivates physicians throughout their careers in medicine?

Abstract: Motivation provides direction and purpose in physicians' work, and motivating factors vary during different career stages. Motivation theories divide sources of motivation into those intrinsic to the work, such as the opportunity for self-expression and intellectual challenge, and those extrinsic to the work, such as salary and time. Although much attention has focused on minimizing negative extrinsic factors, the authors argue that career resilience requires that physicians reflect on and define the sources o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 61 publications
3
38
0
2
Order By: Relevance
“…4,11,21 In any field, smart individuals will take note of what is rewarded and will direct their activities accordingly. 22,23 As a result, many academic faculty elect to limit their time spent in teaching and in clinical care so as to spend greater time on the activity that brings acknowledgement and reward. 2,24 The faculty are a medical school's most precious resource, and therefore, all should be made to feel valued and appreciated.…”
Section: Discussionmentioning
confidence: 99%
“…4,11,21 In any field, smart individuals will take note of what is rewarded and will direct their activities accordingly. 22,23 As a result, many academic faculty elect to limit their time spent in teaching and in clinical care so as to spend greater time on the activity that brings acknowledgement and reward. 2,24 The faculty are a medical school's most precious resource, and therefore, all should be made to feel valued and appreciated.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Intrinsic motivating factors have received relatively scant attention because medical educators and practitioners have thought it too difficult to design institutional strategies and interventions that address stable physician characteristics. [24][25][26] Instead policymakers have tended to focus on extrinsic factors that are more readily manipulated. Several studies of other professions (e.g., nursing, teaching) suggest that intrinsic motivators make particular extrinsic factors salient 27,28 and thereby indirectly affect career satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…18 Insofar as working in primary care or underserved communities does not necessarily promise a "controllable lifestyle" or higher salaries compared to other specialties, physicians-in-training who choose such work may have other intrinsic motivations that overcome these financial disincentives. 19 One such reason can be a strong sense of vocational identity or "calling" toward such work. 20,21 In this study, we also found that male students and allopathic medical students without previous work in medically underserved settings were less likely to report strong vocational identities.…”
Section: Discussionmentioning
confidence: 99%